Digitalisasi Produksi Olahan Kunyit Asam: Meningkatkan Nilai Tambah Dan Kualitas Produk Di Era Industri 4.0 - Kusufa, Roni Alim Ba'diya; Firdaus, Riril Mardiana; Dwanoko, Yoyok Seby; Meviana, Ika; Saputra, Rizal Dwi (Jurnal ABM Mengabdi, 2025)
The processing of tamarind turmeric as a traditional herbal drink has great potential for development in Indonesia. However, MSME actors still face various challenges, such as limited technology, low production efficiency, and restricted market access. This research aims to analyze the role of digitalization in enhancing the added value and quality of processed turmeric products in the era of Industry 4.0. Digitalization not only accelerates the production process through automation but also ensures better quality standards, including in terms of cleanliness, food safety, and product consistency. The purpose of this activity is to help resolve the issues faced by the MSME Tirtha Shanum, specifically regarding the production of turmeric and tamarind products. The approach offered to assist partners with their issues is Participatory Learning and Action (PLA). The steps of the Participatory Learning and Action (PLA) approach are characterized by socialization, discussion, and hands-on training practices. The research location was determined purposefully, namely the Tirtha Shanum MSME. Based on the results of this study, digitalization has proven to be an effective solution in enhancing efficiency, quality, and market access for processed tamarind products. Thus, digitalization becomes an important step in the development of tradition-based products that can compete in the modern era.